2019
DOI: 10.1093/ageing/afz105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between multicomponent and simultaneous dual-task exercise interventions in long-term nursing home residents: the Ageing-ONDUAL-TASK randomized controlled study

Abstract: Background the potential benefits of dual-task interventions on older adults living in long-term nursing homes (LTNHs) from a multidimensional perspective are unknown. We sought to determine whether the addition of simultaneous cognitive training to a multicomponent exercise program offers further benefits to dual-task, physical and cognitive performance, psycho-affective status, quality of life and frailty in LTNH residents. Design: a single-blind randomized controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 26 publications
2
61
0
3
Order By: Relevance
“…No differences between the groups were found in working memory, executive function or episodic memory. Rezola-Pardo et al (2019) reported no additional benefits of simultaneous training compared to physical exercise alone on a range of cognitive, physical and psychosocial outcomes in people living in long-term nursing homes. In Parkinson’s disease, two studies reported no cognitive or physical benefits of exergaming compared to physical exercise (Pompeu et al, 2012) or passive control (Song et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…No differences between the groups were found in working memory, executive function or episodic memory. Rezola-Pardo et al (2019) reported no additional benefits of simultaneous training compared to physical exercise alone on a range of cognitive, physical and psychosocial outcomes in people living in long-term nursing homes. In Parkinson’s disease, two studies reported no cognitive or physical benefits of exergaming compared to physical exercise (Pompeu et al, 2012) or passive control (Song et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…A list of the excluded studies (with reasons) is provided in Appendix C. Two additional eligible studies were identified through manual search (Adcock et al, 2020; Rezola-Pardo et al, 2019). Thus, a total of 47 studies fulfilled inclusion criteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies show that dual-task training is not always more beneficial than e.g. multicomponent exercises to gain positive effects on cognitive-motor performance in older adults [ 43 45 ]. To become more effective in improving dual-task performance, intervention programs should include a combination of complex balance and coordination tasks [ 46 ].…”
Section: Introductionmentioning
confidence: 99%